Penggunaan Metode Diskusi Mata Pelajaran PKN dalam Meningkatkan Kemampuan Mengeluarkan Pendapat pada Siswa Kelas V SD Inpres Daeo Kecamatan Morotai Selatan - Subhan Hayun (Jurnal Ilmiah Wahana Pendidikan, 2019)
This research is a research on the use of discussion method which aims to study the use of discussion methods in fifth grade students of SD Inpres Daeo Kec. Selatan Morotai. This type of research is a type of descriptive qualitative research that discusses the application of learning by the method of discussion. Why this method teaches learning in problems that occur in learning by way of discussion about learning solutions most students think about learning that involves activities that involve many students who think sitting in the classroom like a meeting place. Therefore designing a learning process that satisfies students is one aspect of the environment that provides guidance that provides a sense of security in the learning process in class. The role and supervision of the teacher in the learning process by using the method of discussion and giving encouragement and motivation to students to learn is a very important factor in order to achieve learning objectives. After the teacher uses the discussion method so that the fifth grade students of SD Inpres Daeo are able to express their opinions.